2019
DOI: 10.1016/j.stemcr.2019.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Defined Media Can Maintain Pig Pluripotency Network In Vitro

Abstract: Summary Pig embryonic stem cells (pESCs) have been considered an important candidate for preclinical research on human therapies. However, the lack of understanding of pig pluripotent networks has hampered establishment of authentic pESCs. Here, we report that FGF2, ACTVIN, and WNT signaling are essential to sustain pig pluripotency in vitro . Newly derived pESCs were stably maintained over an extended period, and capable of forming teratomas that contained three germ layers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 48 publications
8
73
0
Order By: Relevance
“…But, patterns of NANOG in pig pluripotent stem cells (PSCs) from pre-implantation embryos are different from pig iPS cells. NANOG is highly expressed in pig ES cells from ICM/epiblast [13] and in pig EPS cells [12]. The NANOG expression of pig iPS cells in doxycycline-inducible system with 4 factors (OSKC) was low [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But, patterns of NANOG in pig pluripotent stem cells (PSCs) from pre-implantation embryos are different from pig iPS cells. NANOG is highly expressed in pig ES cells from ICM/epiblast [13] and in pig EPS cells [12]. The NANOG expression of pig iPS cells in doxycycline-inducible system with 4 factors (OSKC) was low [36].…”
Section: Discussionmentioning
confidence: 99%
“…NANOG is also highly expressed in pig preimplantation embryos [10]. Recently, pig pluripotent stem cells (PSCs) were established from the inner cell mass of pig blastulas [11][12][13]. We found that induced pluripotent stem cells (iPSCs) from pigs express NANOG heterogeneously [14], as in mouse PSCs [15,16].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies showed that ESCs were more efficient for cloning of mouse than differentiated cells such as immune cells, neuron, and fibroblasts (Hochedlinger and Jaenisch, 2002). which indicates that these cells could have the potential for preclinical study of human cell therapy (Choi et al, 2019). And they found lipid supplementation was crucial for maintaining pig pluripotency in vitro, which indicated that metabolic niche also affects deriving and maintaining pluripotency in the ungulate.…”
Section: Large Animal Models In Stem Cell Biology: a Pig Reviewmentioning
confidence: 99%
“…To accomplish these goals with pig PSCs, there are hurdles remain to be overcame. First of all, although recent study represented authentic pig ESCs can derive using chemically defined media (Choi et al, 2019), it is required to develop more defined culture conditions such as feeder-free culture and reprogramming method for pig PSCs. Analysis of enhancer showed that different transcription factors were involved in the expression of OCT4 known as a core gene of pluripotency networks , which means a majority of pig pluripotency circuit remains to be elucidated.…”
Section: Perspectivesmentioning
confidence: 99%